2019
DOI: 10.1038/s41598-019-48743-8
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran extract supplement improves sleep efficiency and sleep onset in adults with sleep disturbance: A randomized, double-blind, placebo-controlled, polysomnographic study

Abstract: We previously reported that rice bran extract supplement (RBS) administration to mice decreased sleep latency and induced non-rapid eye movement (NREM) sleep via inhibition of the histamine H 1 receptor. Based on this, we performed the first clinical trial to investigate whether RBS would be beneficial to subjects with disturbed sleep. We performed a randomized, double‐blinded, placebo‐controlled, 2-week study. Fifty subjects with sleep disturbance were enrolled and received either RBS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The RBS (Lot No. SD-RB-002) standardized with 0.45% γ-oryzanol was obtained from S&D Co., Ltd. (Cheongju, Korea) as previously described [ 19 20 21 ]. Briefly, rice bran ( O. sativa L.) was extracted in an ethanol/water solution at 40°C for 8 h. The ethanol extract was filtered, concentrated, and spray-dried for storage.…”
Section: Methodsmentioning
confidence: 99%
“…The RBS (Lot No. SD-RB-002) standardized with 0.45% γ-oryzanol was obtained from S&D Co., Ltd. (Cheongju, Korea) as previously described [ 19 20 21 ]. Briefly, rice bran ( O. sativa L.) was extracted in an ethanol/water solution at 40°C for 8 h. The ethanol extract was filtered, concentrated, and spray-dried for storage.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, once anxiety symptoms occur from sleep deprivation, this kind of vicious sleep disruption will hamper the therapeutic efficacy in anxiety patients. Therefore, proper and safe supplementary nutrients are needed for anxiety relief while improving sleep patterns in anxious patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tart cherry juice consumption for 7 days has shown to significantly increase total sleep time and sleep efficiency ( 40 ). In another study, significant improvement in sleep efficiency was reported when a rice bran extract was supplemented for 14 days at 1000 mg/day ( 41 ). These studies justify our protocol involving 7 days’ supplementation to investigate the influence of BCO-5 on sleep.…”
Section: Discussionmentioning
confidence: 99%